Association of long-term exposure to traffic-related PM10 with heart rate variability and heart rate dynamics in healthy subjects. (April 2019) - Meier-Girard, Delphine; Delgado-Eckert, Edgar; Schaffner, Emmanuel; Schindler, Christian; Künzli, Nino; Adam, Martin; Pichot, Vincent; Kronenberg, Florian; Imboden, Medea; Frey, Urs; Probst-Hensch, Nicole
Abstract: Background: Epidemiological evidence on the influence of long-term exposure to traffic-related particulate matter (TPM10 ) on heart rate variability (HRV) is weak. Objective: To evaluate the association of long-term exposure (10 years) with TPM10 on the regulation of the autonomic cardiovascular system and heart rate dynamics (HRD) in an aging general population, as well as potential modifying effects by the a priori selected factors sex, smoking status, obesity, and gene variation in selected glutathione S-transferases (GSTs). Methods: We analyzed data from 1593 SAPALDIA cohort participants aged ≥ 50 years. For each participant, various HRV and HRD parameters were derived from 24-hour electrocardiogram recordings. Each parameter obtained was then used as the outcome variable in multivariable mixed linear regression models in order to evaluate the association with TPM10 . Potential modifying effects were assessed using interaction terms. Results: No association between long-term exposure to TPM10 and HRV/HRD was observed in the entire study population. However, HRD changes were found in subjects without cardiovascular morbidity and both HRD and HRV changes in non-obese subjects without cardiovascular morbidity. Subjects without cardiovascular morbidity with homozygous GSTM1 gene deletion appeared to be more susceptible to the effects of TPM10 . Conclusion: This study suggests that long-term exposure to TPM10 triggers adverse changes in the regulation of the cardiovascular system. These adverse effects were more visible in the subjects without cardiovascular disease, in whom the overall relationship between TPM10 and HRV/HRD could not be masked by underlying morbidities and the potential counteracting effects of related drug treatments. Highlights: Long-term exposure to TPM10 triggers adverse effects on the heart function. Evidences of such adverse effects were found in healthy subjects. Homozygous GSTM gene deletion appears to be an effect modifier of TPM10 .